2021
DOI: 10.1038/s41598-021-89819-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of preconception care and its association with family planning utilization among women in Ethiopia: meta-analysis

Abstract: Preconception care (PCC) increases the chance of couple’s being healthy and having a healthier baby. It is an important strategy to prevent maternal and perinatal complications. The level of knowledge on preconception care increases its uptake. It is also considered as an input for further intervention of reduction in maternal and neonatal mortality enabling progress towards sustainable development goals (SDGs). Therefore, this systematic review and meta-analysis aimed to estimate the pooled knowledge level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
3
0
2
Order By: Relevance
“…In SSA, one-third (33.27%) of women in the reproductive age group had good knowledge about PCC. This finding was aligned with two studies conducted in Ethiopia and Utah 37 , 42 , 43 but lower than a systematic review and meta-analysis conducted of studies from across the world, including Saudi Arabia, China, and Kenya. 13 , 44 – 46 Women’s knowledge of PCC seemed to vary across countries, with some countries reported to have PCC guidelines and routinely practiced PCC.…”
Section: Discussionsupporting
confidence: 77%
“…In SSA, one-third (33.27%) of women in the reproductive age group had good knowledge about PCC. This finding was aligned with two studies conducted in Ethiopia and Utah 37 , 42 , 43 but lower than a systematic review and meta-analysis conducted of studies from across the world, including Saudi Arabia, China, and Kenya. 13 , 44 – 46 Women’s knowledge of PCC seemed to vary across countries, with some countries reported to have PCC guidelines and routinely practiced PCC.…”
Section: Discussionsupporting
confidence: 77%
“…In the same vein, age and good knowledge of PCC showed significant association with utilisation. 20 , 21 The current review aimed to be more inclusive, with no restrictions on setting and PCC provision. As a result, the goal of this review was to systematically map out evidence on the current state of PCC knowledge, utilisation and provision among women and HCWs in SSA in the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…11 12 In addition, a recent meta-analysis conducted in Ethiopia has found that utilisation of family planning had a positive impact on women's knowledge of preconception care. 26 However, inconsistent findings on the associations of preconception care with utilisation of family planning and previous adverse birth outcomes have not been systematically reviewed in Ethiopia. Thus, this review aims to estimate the pooled association of preconception care with utilisation of family planning and previous adverse birth outcomes in Ethiopia.…”
Section: Open Accessmentioning
confidence: 99%